2006
DOI: 10.1523/jneurosci.2101-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Representation in the Human Medial Temporal Lobe

Abstract: Recent experiments characterized individual neurons in the human medial temporal lobe with remarkably selective, invariant, and explicit responses to images of famous individuals or landmark buildings. Here, we used a probabilistic analysis to show that these data are consistent with a sparse code in which neurons respond in a selective manner to a small fraction of stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
170
5
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(182 citation statements)
references
References 20 publications
6
170
5
1
Order By: Relevance
“…However, these studies involved tasks in which memories were acquired over an extended period (allowing for the development of place fields), not tasks in which multiple memories were formed in rapid succession on a single trial. The same is true of prior evidence for sparse coding of semantic memory in the human medial temporal lobe (11). Our findings suggest that, as has long been predicted, rapidly formed episodic memories are supported by a sparse distributed code in the human hippocampus.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, these studies involved tasks in which memories were acquired over an extended period (allowing for the development of place fields), not tasks in which multiple memories were formed in rapid succession on a single trial. The same is true of prior evidence for sparse coding of semantic memory in the human medial temporal lobe (11). Our findings suggest that, as has long been predicted, rapidly formed episodic memories are supported by a sparse distributed code in the human hippocampus.…”
Section: Discussionsupporting
confidence: 87%
“…Previous work with humans has suggested that the representation of semantic memory in the hippocampus is relatively sparse (11). In addition, one study (10) found that episodic memory of a particular video clip (tested using recall) was preceded by the selective reactivation of the same neuron that had reliably responded to the presentation of that clip on an earlier test of semantic memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the idea that the MTL represents information using a sparse code is one of the basic tenets of most contemporary memory models (17)(18)(19). Given that the MTL assigns a relatively small number of neurons to a specific stimulus (20), and that the number of stimuli in the environment is very large, does a feature such as personal relevance, which may be related to the incidental recollection of autobiographically significant information (3), make a stimulus more likely to elicit a selective excitatory response from a cell? Here, we address the question of whether individual neurons in the MTL show a preference for personally relevant pictures.…”
mentioning
confidence: 99%
“…Indeed, even when a neuron in a given experiment responds to only one out of many images tested, it is assumed (quite plausibly) that it would fire to some other (untested) images (e.g. Waydo, Kraskov, Quiroga, Fried, & Koch, 2006). Accordingly, the most striking examples of selective neural responding are often taken as evidence for highly sparse and selective coding rather than for grandmother cells.…”
Section: Prefacementioning
confidence: 99%